Locating the Jewish Future : The Restoration of Looted Cultural Property in Early Postwar Europe - Gallas, Elisabeth (Naharaim, 2015)
At the end of World War II Allied soldiers found an unexpected amount of looted cultural property on German territory, property that had originally belonged to Jewish institutions and private owners from all over Europe. To take care of this precious booty the American Military Government for Germany organized an unprecedented initiative in cultural restitution. However, since most of the Jewish treasures found were heirless, traditional legislation based on bilateral intergovernmental regulations was insufficient for the task of finding just restitution solutions and meeting Jewish collective interests. In 1949, after complex legal negotiations, the New York based corporation Jewish Cultural Reconstruction (JCR) was officially installed to act as trustee for heirless Jewish cultural property found in the American Zone of Occupation. Not only was it extraordinary that the major Jewish organizations of the time – representing Palestine/Israel as well as the Diaspora – worked together via JCR, this was also the first time that international law recognized a legal representative of the Jewish collective. This paper explores the history of JCR, focusing, in particular, on the manifold and conflicting perceptions of the future of Jewish existence post-1945 that informed its work. On the one hand, the reestablished Jewish communities of Europe, especially the one in Germany, strongly contested JCR’s goal of distributing the rescued material to Jewish centers outside of Europe. Unlike JCR, they believed in a new Jewish beginning on the war-torn continent. On the other hand, Zionist- versus Diaspora-centered views also led to internal conflicts within JCR regarding the rightful ownership and appropriate relocation of European Jewish cultural heritage. JCR’s history reveals significant facets of Jewish agency and future planning in the early postwar years while reflecting the new topography of Jewish existence after the Holocaust.